Longevity of bonded composite restorations after dentin biomodification with neolignans obtained from Nectandra leucantha - Guedes, Mateus Henrique de Godoy; Maia, Marcelo Henrick Matochek; Graeff, Carlos Frederico de Oliveira; González, Alejandra Hortencia Miranda; Grecco , Simone dos Santos; D'Alpino, Paulo (Brazilian Dental Science, 2022)
Objective: This in vitro study evaluated the effect of neolignan-containing solutions on dentin biomodificationpreviously applied to the bonding procedure in adhesive restorations. Material and Methods: Neolignans,dehydrodieugenol B–CP1 and dehydrodieugenol B methyl ether–CP2, were isolated from Nectandra leucanthaand two aqueous solutions containing 0.13% neolignans, 0.2% propylene glycol and 3.0% ethanol were prepared.Bovine teeth were ground flat to obtain 2-mm thick specimens which received resin composite restorations(N=10). The neolignan solutions were applied before the bonding procedure (60 s). Experimental groups were:control, untreated group, 0.12% chlorhexidine gel, 0.13% CP1 solution, and 0.13% CP2 solution. A push-outbond strength test was conducted (0.5 mm/min). Bovine tooth sections (0.5×1.7×7.0 mm) were also obtained toassess the modulus of elasticity and mass change after treatment (N=15). A three-point bending test evaluated theelastic modulus of fully demineralized dentine beams after immersion in the solutions. The data were statisticallyanalyzed (a = 0.05). Results: The bond strength of the restorations to dentin was significantly improved by thetreatment with neolignan-containing solutions, irrespective of the evaluation time (p0.05), butthe means were significantly higher than the control groups (p